Behavior Of Stock Exchange Investors In Lampung - Winda Rika Lestari; Wahyu Kuntarti (Jurnal Ilmiah ESAI, 2014)
Stock exchange is a venue for companies to find out some finance to support their business. The trading activities in this field come up with high level uncertainties which are potential to shape various behaviors of the investors. Stock exchange investors sometimes behave irrationally by showing certain action taken on the bases of judgment deviated from rational assumptions. Theoretically, someone’s actions are derived or shaped by his or her basic needs which are developed under the influence of his or her environment where he or she works or lives. Hence, psychological factors can also shape the investors’ behavior in doing the transactions in the stock market. According to the result of the analysis carried out in the research, the 23 initial constructs analyzed can be reduced into seven factors having cumulative variance value 69,952% that can be used to explain the behavior of investors in investing. Those factors are relationship and experiences, convenience, greed, reality, trust and safety, profit orientation, and emotion. Based on the statistical logistic regression test, it is known that Ho is accepted with significance number 0,899 (>0,05), which means that those factors can be used to predict the behavior of the investors in facing the risks. In addition, based on the independent sample t-test, it is known that the significance number of the six out of the seven factors is bigger than 0,05, which means Ho cannot be rejected. It can be explained that there is no significant difference among the six factors shaping the female and male investors in Lampung stock exchange. There is only emotion factor which shows the significance number bigger than 0,05. It means emotion factor of female and male investors is different. It can be concluded that the fourth hypothesis of the research is rejected.Keywords : behavior, finance, stock exchange